2021
DOI: 10.1055/s-0041-1724132
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Joint Line Elevation on In Vivo Knee Kinematics in Bicruciate Retaining Total Knee Arthroplasty

Abstract: Prior studies have reported a negative effect on both clinical outcomes and patient-reported outcome measures (PROMS) following joint line elevation (JLE) in cruciate-retaining (CR) total knee arthroplasty (TKA) and posterior stabilized (PS) TKA designs. This experimental study was aimed to quantify the effect of JLE on in vivo knee kinematics in patients with bicruciate retaining (BCR) TKA during strenuous activities. Thirty unilateral BCR TKA patients were evaluated during single-leg deep lunge and sit-to-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Although the apparent overall joint line changes are small, this is consistent with knee arthroplasty literature noting knee joint line elevation as small as 2.6 and 2.3 mm resulting in a clinically significant loss in PROMs and maximum flexion angles, respectively. 25 This suggests an increased need to improve surgical precision to optimize patient outcomes following TAA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the apparent overall joint line changes are small, this is consistent with knee arthroplasty literature noting knee joint line elevation as small as 2.6 and 2.3 mm resulting in a clinically significant loss in PROMs and maximum flexion angles, respectively. 25 This suggests an increased need to improve surgical precision to optimize patient outcomes following TAA.…”
Section: Discussionmentioning
confidence: 99%
“…Although not yet studied in the ankle, femoral joint line restoration has been identified as a major determinant of postoperative ROM following total knee arthroplasty with elevation of the joint line resulting in patella baja and decreased ROM. 3,18,34 A recent study by Klemt et al 25 reported a linear negative correlation between joint line elevation in both in vivo knee kinematics and PROMs. Specifically, knee joint line elevation of greater than 2.6 and 2.3 mm resulted in a clinically significant loss in PROMs and maximum flexion angles, respectively.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Joint line changes after TKA have an influence on range of motion (ROM), patella height, and mid-flexion laxity [7][8][9], and thereby TKA has generally been performed by cutting the distal femur, under consideration of the implant thickness, without changing the joint line and patella height. Bone gap was measured after conventional cutting of distal femur and proximal tibia, revealing an increase in flexion gap as compared with that after setting the implant.…”
Section: Introductionmentioning
confidence: 99%